Experimental research into impact of kinematic and design parameters of a spiral potato separator on quality of plant residues and soil separation - Ruzhylo, Z.; Bulgakov, V.; Adamchuk, V.; Bondarchuk, A.; Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич; Krutyakova, V.; Olt, J. (My University, 2020)
The experimental investigations carried out in field production conditions have proved that the process of cleaning potato tubers from extraneous material with the use of a spiral separator takes place due to the active conveyance of the heap by the turns of the cantilever mounted cleaning spiral springs. The cleaning spiral springs not only rotate at the set angular velocity, but simultaneously their cantilevered ends perform oscillatory motion, which arises due to the deflection of their longitudinal axes under the action of the weight of the potato heap fed into the work zone of the separator. The results obtained in the process of the field experiment investigations carried out by the authors have provided for obtaining the relations that enable selecting the optimum design and kinematic parameters of the spiral-type potato cleaning devices for the targeted separation rate and, accordingly, estimating their impact on the quality of the performed work process.
Keywords: process of cleaning potato; spiral separator; cleaning spiral springs